Svenska musikfester och Nordensvärmeri i Tyskland.: Dortmund 1912 och Stuttgart 1913 - Leiska, Katharine (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2005)
Swedish Music Festivals and passion for the north in Germany. Dortmund 1912 and Stuttgart 1913 During the reign of Wilhelm II (1888–1918) a passion for an utopian landscape called “Nordland” – geographically equated with Scandinavia – influenced German political life and literature. During this period two music festivals called “Schwedisches Musikfest” were arranged, first 1912 in Dortmund, thereafter 1913 in Stuttgart. These festivals were the result of a collaboration between German and Swedish musicians and music lovers. The music played was exclusively written by Swedish composers. Hugo Alfvén, Tor Aulin and the violinist Henri Marteau played key roles. Though other factors such as personal friendship between some of the musicians, were important motives for initiating the festivals, the passion for “Nordland” was crucial to both their arrangement and the German reception of the music played. The passion did not influence the Swedish committee, which compiled the musical programme, yet it did influence the German sponsors. Especially the idea of being of the same ancestry as the Swedes (“Stammverwandtschaft”) affected those entrepreneurs. The reception of the music, as it is represented in daily newspapers and music magazines, was dominated by the idea that the music should sound nationally “Nordic” or “Swedish” (those words were used synonymously). This expectation of a genuine Nordic sound was generated by the image of “Nordland” and by earlier reception of Scandinavian culture.